2021
DOI: 10.18805/ijare.a-626
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of N Mineralization and Nutrient Uptake of Tithonia diversifolia and Saccharum officinarum Leaves in Sandy Loam Soil

Abstract: Background: This study aimed to determine the pattern of N mineralization of tithonia (Tithonia diversifolia) and sugarcane (Saccharum officinarum) leaves and assess the uptake of N nutrients in maize by giving T. diversifolia and S. officinarum leaves with different qualities on sandy loam soil. Methods: The research used a completely randomized design (CRD) with following treatment: T1 (100% T. diversifolia), T2 (100% S. officinarum), T3 (75% T. diversifolia: 25% S. officinarum), T4 (50% S. officinarum: 50% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The high uptake of K in the T1 treatment was related to the K nutrient content in T1 (3.62%), which was higher than the other treatments (Table 1). In addition to P and K nutrient uptake, Tithonia diversifolia treatment also increased N uptake in maize, in which N nutrient uptake with Tithonia diversifolia and its combination with sugarcane leaves was able to increase N uptake by 125,98 % to 144.54% (Farni et al, 2021 ). Farni et al (2021) reported that the highest cumulative N release was found in T1 treatment (517.15 mg plant -1 ).…”
Section: Maize Growth and Nutrient Uptakementioning
confidence: 93%
See 2 more Smart Citations
“…The high uptake of K in the T1 treatment was related to the K nutrient content in T1 (3.62%), which was higher than the other treatments (Table 1). In addition to P and K nutrient uptake, Tithonia diversifolia treatment also increased N uptake in maize, in which N nutrient uptake with Tithonia diversifolia and its combination with sugarcane leaves was able to increase N uptake by 125,98 % to 144.54% (Farni et al, 2021 ). Farni et al (2021) reported that the highest cumulative N release was found in T1 treatment (517.15 mg plant -1 ).…”
Section: Maize Growth and Nutrient Uptakementioning
confidence: 93%
“…In addition to P and K nutrient uptake, Tithonia diversifolia treatment also increased N uptake in maize, in which N nutrient uptake with Tithonia diversifolia and its combination with sugarcane leaves was able to increase N uptake by 125,98 % to 144.54% (Farni et al, 2021 ). Farni et al (2021) reported that the highest cumulative N release was found in T1 treatment (517.15 mg plant -1 ). The high nutrient uptake in 100% tithonia leaves and its combination with sugarcane leaves was due to high N content and low C/N ratio of tithonia leaves (Table 1) so that the decomposition and nutrient release rates were high (Li et al, 2011;Kaleeem Abbasi et al, 2015;Wang et al, 2017).…”
Section: Maize Growth and Nutrient Uptakementioning
confidence: 93%
See 1 more Smart Citation
“…Alternatively, plants subjected to ON reached average heights of 3.09 m at the dose of 5.6 T ha −1 in crop season 1 (2019/2020). This yield is directly due to the mineralization of these organic residues, which makes N available to the soil and contributes to the improvement of biometric parameters [21,22,36,37].…”
Section: Application Of Different Doses Of Mn or On Affects The Growt...mentioning
confidence: 99%